The Influence of Social Media on Criminal Defamation in Indonesia - Ramadhan, Muhammad; Kusno, Kusno; Ansyari Siregar, Ahmad (International Journal Labs, 2024)
The purpose of this study is to explore and understand the legal arrangements related to criminal defamation through social media, which are reviewed based on Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE), as well as analyzing the application of the law against perpetrators of criminal defamation through social media. The research method used in this research is the normative juridical method, which refers to theoretical and normative legal analysis based on applicable laws and regulations. The discussion results show that the legal regulation of criminal defamation through social media has been regulated in Article 45 paragraph (3) of the ITE Law, which regulates criminal sanctions for perpetrators who intentionally and without the right to disseminate information or electronic documents containing insults or defamation. The application of the law related to criminal defamation on social media can also be seen in court decisions, for example, in the Decision of the Rokan Hilir District Court Number 649/PID.SUS/2019/PN-RHL. In the verdict, the Defendant was found guilty and sentenced to imprisonment and a fine by the applicable provisions. The results of this study imply that ITE law provides a strong foundation for dealing with criminal defamation on social media. The application of the law has been proven through court decisions based on the provisions of the current law. This shows the importance of supervision and law enforcement against behavior that harms others through social media to prevent similar criminal acts in the future.